INCLUSIVE EDUCATION IN PHYSICAL EDUCATION: METHODS AND APPROACHES TO TEACHING STUDENTS WITH DISABILITIES (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
The article deals with the topical aspects of inclusive physical education aimed at teaching students with disabilities. The existingmethods and techniques used to organize inclusive physical education classes are analyzed, focusing on curriculum adaptation andindividual approach to each student. The article offers practical recommendations for the implementation of inclusivemethodologies in the educational process, including the use of modern technologies and active learning methods.